From bumps in the road to the edge of chaos: The nature of change in adults - Keenan, Elizabeth King (Journal of Social Work, 2011)
This article explores the question of how human beings change, how change is constrained, and how change emerges out of and subsequently creates new forms of stability with adults. The emergence of Dynamic Systems Theories (DST) from developmental biology and neuroscience provide the tools to engage in such an understanding by attending to the issues of time, balance, influencing parameters (within person and sociocultural and material environments), and multiple adaptive and maladaptive pathways. DST provides the framework to understand the dynamic processes of bio-psychosocial factors that provide human beings with the stability and the flexibility to navigate the challenges and stressors of living. Complexity, the ability to experience inner continuity as one is changing, is a fluid balance that supports effective functioning. Findings: Key principles and concepts of DST describe multiple pathways of stability and change. A case example illustrates how DST helps social workers understand client experiences and responses to stressors, formulate initial and ongoing assessments, and monitor clients' participation in change activities. Application: Social workers seek to help people who experience an imbalance due to an inability to effectively respond to the negative impact of a stressor. By understanding the various pathways of balance and imbalance along the continuum of continuity to change, social workers can better understand how stressors are impacting specific clients, and subsequently the kinds of change that would best assist each client.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-526-918-145-29X tex.type: [object Object]
Keywords: change; complexity theory; dept.swk; dynamic systems theory; peer-reviewed; self-organization; stressors

Seeing the forest and the trees: using dynamic systems theory to understand “Stress and coping” and “Trauma and resilience” - Keenan, Elizabeth King (Journal of Human Behavior in The Social Environment, 2010)
Although research is beginning to capture the complex interactions of biopsychosocial variables operating within experiences of stressors and trauma, the bodies of research have remained largely separate and limited. This study describes a scaffold of factors and pathways based on principles from dynamic systems theories (DST) to organize the literatures on stress and coping and trauma and resilience. As a process model, DST provides the language to understand both impact and response to stressors and trauma: Not as a list of symptoms but as interactive processes within persons and between persons and their surroundings. © Taylor & Francis Group, LLC.
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-271-426-334-225 tex.type: [object Object]
Keywords: Complexity theory; Dynamic systems theory; Stress and coping; Trauma and resilience; dept.swk; peer-reviewed

Applying research to enhance capacity: A unifying purpose for an integrated profession - Keenan, Elizabeth King (Journal of Social Work Education, 2016)
For more than a century the social work profession has had a dual purpose: to promote individual well-being and social justice, but the micro-macro divide is fragmenting the profession. This article suggests that the profession's aim might best be realized by adopting a unifying purpose, a just sense of well-being. Research on complex adaptive systems conceptualizes a unifying purpose as vertical integration carried out in differentiated ways in discrete moments of practice in various settings. Interpersonal neurobiology and Aristotle's interdependence of character virtues and practical judgment inform a corresponding shift from the dualities of personal and professional to the social worker as a person with differentiated professional capacities and activities. Integration with differentiation enhances capacity to promote the profession's purpose.
1 citations (Crossref) [2023-10-31] tex.eissn: 2163-5811 tex.unique-id: ISI:000381004400007
Keywords: dept.swk; differentiation; human; human experiment; morality; neurobiology; occupation; peer-reviewed; social justice; social work; wellbeing

Navigating the ethical terrain of spiritually focused psychotherapy goals: multiple worldviews, affective triggers, and personal practices - Keenan, Elizabeth King (Smith College Studies in Social Work, 2010)
Constructing mutual, spiritually focused psychotherapy goals is a practice activity fraught with numerous ethical and countertransferential challenges. This article seeks to inform the thinking and enhance the ability of clinical social workers to engage in collaborative and responsive dialogues with their clients regarding the goals of spiritually focused clinical practice by (1) identifying the multiple value frameworks that influence decisions regarding practice goals, (2) articulating some of the ethical complexities and common countertransferential reactions associated with goal setting, and (3) providing self-reflection questions and guides to help therapists navigate the complexities of this material.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-323-659-562-624 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: Countertransference; Ethics; Goals; Piritually focused psychotherapy; dept.swk

Working models: A tool for synthesizing psychology, culture, and power in everyday experiences and internal representations - Keenan, Elizabeth King (Smith College Studies in Social Work, 2003)
As social beings, we experience ourselves through interactions with others in daily routines that participate in the cultural practices and power relations of broader social structures. Social workers, and social scientists in general, however, have had difficulty conceptualizing and synthesizing this way of being in the world. This paper attempts to respond to that gap by discussing how clinical social workers can use the concept of working models as a tool for listening and understanding in psychotherapy. Utilizing a case example, the paper will discuss three working models, the enactment of power relations, cultural practices, and psychological processes, which provide an integrative framework to inform clinical work.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-182-490-831-257 tex.type: [object Object]
Keywords: dept.swk

Re/Un/Discover: An embodied heuristic for uncertainties in social work practice - Keenan, Elizabeth King (Australian Social Work, 2021)
Social workers have always worked with and within uncertainties in practice, but the COVID-19 pandemic is amplifying the frequency and degree of uncertainty across ecological levels. Social workers need enhanced capacity to work with these uncertainties and the impact on individual and collective wellbeing. The RE/UN/DIScover heuristic guides social workers’ responses to the wide range of practice uncertainties experienced in the moment and over time. Drawing on understandings of embodied wellbeing from interpersonal neurobiology and the power relations manifest in intersectional positionality, RE/UN/DIScover offers embodied, iterative practices to access the wealth of capabilities within self and others. IMPLICATIONS Disruptions and uncertainties connected with pandemics, economic recessions, continued systemic injustices and other human-made problems can challenge social workers and impact the wellbeing of individuals and communities. Heuristics are guides that sort, order, and inform decisions and actions. The RE/UN/DIScover heuristic uses knowledge about embodied wellbeing and various forms of power to guide social workers. RE/UN/DIScover offers social workers practices to use with uncertainties both in the moment and over time. © 2020 Australian Association of Social Workers.
3 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097057855
Keywords: dept.swk; peer-reviewed

Walking the Walk or Just Talking the Talk?: An Exploratory Study of the Ways Social Workers Understand Social Work Practice - Keenan, Elizabeth King (2015)
Keywords: dept.swk; faculty_collection

Sabbatical Leave Report: Sabbatical Spring, 2015 - Keenan, Elizabeth King (Distribution: Spring ; Social Work., 2015)
From the report: "Project title: Walking the walk or just talking the talk? An exploratory study of the ways social workers understand social work practice." The report describes the research problem, identifies three reserach questions, and discusses the project outcomes and reporting.
Keywords: dept.swk; faculty_collection; sabbatical_report

Theorizing the Emergence of Change in Daily Living: Developing a Contextual Framework for Social Work Practice. - Keenan, Elizabeth King (2008)
Keywords: dept.swk; faculty_collection; sabbatical_report

RE/UN/DIScover Heuristic: Working with Clinical Practice Impingements in Dehumanizing Times - Keenan, Elizabeth King (Clinical Social Work Journal, 2023)
Although clinical social work seeks to center the transformative potential of human relationships, practitioners are experiencing heightened systemic and organizational impingements from the dehumanizing pressures of neoliberalism. Neoliberalism and racism diminish the vitality and transformative potential of human relationships, disproportionately affecting Black, Indigenous and People of Color (BIPOC) communities. Practitioners are also experiencing increased stress and burnout related to increased caseloads and decreased professional autonomy and organizational practitioner support. Holistic, culturally responsive, and anti-oppressive processes seek to counter these oppressive forces but need further development to synthesize antioppressive structural understandings with embodied relational interactions. Practitioners can potentially contribute to efforts that apply critical theories and antioppressive understandings within their practice and workplace. Through an iterative flow of three sets of practices, the RE/UN/DIScover heuristic supports practitioners’ efforts to respond in those challenging everyday moments where oppressive forms of power are imposed and embedded within systemic processes. With themselves and other colleagues, practitioners engage in compassionate REcover practices; use curious, critical reflection to UNcover full understandings of power dynamics, impacts, and meanings; and draw on creative courage to DIScover and enact socially just and humanizing responses. This paper describes how practitioners can use the RE/UN/DIScover heuristic in two common challenging moments of clinical practice: systemic practice impingements and implementing a new training or practice model. The heuristic seeks to support practitioners’ efforts to preserve and expand socially just, relational spaces for themselves and those with whom they work within the context of systemic dehumanizing neoliberal forces.
Keywords: Clinical practice; Heuristic; Neoliberalism; Power; Practice challenges; Window of tolerance; dept.swk; peer-reviewed

The common factors model: implications for transtheoretical clinical social work practice. - Cameron, Mark; Keenan, Elizabeth King (Social Work, 2010)
Direct practice social workers today are challenged to address the requirements of the complex array of professional, organizational, institutional, and regulatory demands placed on them in the broader socioeconomic context of fewer resources and diminished public support for social welfare services in the United States. The common factors model provides an accessible, transtheoretical, empirically supported conceptual foundation for practice that may help to resolve this conundrum and support effective practice. Common factors are conditions and processes activated and facilitated by strategies and skills that positively influence practice outcomes across a range ofpractice theories. The model provides an expanded conceptualization of the "active ingredients" required for change to include a focus on conditions and processes as well as practice strategies and to focus on all who are involved in the work. The model is described and implications for practice are discussed.
32 citations (Crossref) [2023-10-31] Place: United States Cameron, Mark. Department of Social Work, Southern Connecticut State University, New Haven 06515, USA. cameronm3@southernct.edu
Keywords: *Models; Theoretical; *Social Work/mt [Methods]; Change; Common factors; Empirical; Humans; Professional-Patient Relations; Social Support; Social work practice; Transtheoretical; dept.swk

A new perspective: the common factors model as a foundation for social work practice education - Cameron, Mark; Keenan, Elizabeth King (Journal of Teaching in Social Work, 2009)
Foundation social work practice education is critical to the preparation of BSW practitioners for professional practice and the establishment of a theoretical and skill base upon which graduate students may build competencies in the advanced curriculum. Issues in the foundation practice curriculum may hinder this development. The common factors model holds promise as an organizing framework for foundation social work practice education. This model may help to resolve some key issues in social work and social work education, and may provide a useful, coherent, and empirical base for the foundation practice curriculum. © Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-482-221-756-184 tex.type: [object Object]
Keywords: Common factors; Direct practice; Foundation curriculum; Practice education; dept.swk; peer-reviewed

The Common Factors Model for Generalist Practice - Cameron, Mark; Keenan, Elizabeth King (Pearson Education, 2013)
Keywords: Social work administration; dept.swk; faculty_collection

From silos to scaffolding: engaging and effective social work practice - Keenan, Elizabeth King; Grady, Melissa D. (Clinical Social Work Journal, 2014)
In this final article of the special issue Beyond the Manual: Using Data and Judgment in Clinical Social Work Practice, we extend the discussion regarding the use of data and judgment. We discuss the multiple sources of data used in practice, including research evidence, client perspectives and experience, moment-by-moment process observation, and client feedback regarding progress towards specific, desired outcomes. We move beyond current debates purporting one framework over another to propose a synthesizing framework that situates evidence-based practice, empirically supported interventions and common elements/mapping and adapting practice within a common factors scaffolding framework. This framework provides a way for social workers to effectively make sound judgments using research and client data within the demands of contemporary practice. The article provides a brief overview of the four practice approaches followed by the proposed scaffolding framework and rationale, and concludes with implications for practice, professional education, and research.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-863-792-919-992 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Common elements; Common factors; Empirically supported interventions; Empirically supported treatments; Evidence-based practice; Research evidence; dept.swk

Beyond the manual: using research and evidence in social work practice - Grady, Melissa D.; Keenan, Elizabeth King (Clinical Social Work Journal, 2014)
There is a growing divide in social work between those that believe social work interventions should be based on either art or science. We argue that these positions create a false dichotomy within the profession, possibly due to the language associated with clinical work and research. In this introduction article of the Special Issue: Beyond the Manual, we outline the debate within social work around the art and science split and then offer a new approach to framing the issue. We argue that social workers are regularly approaching their work with clients using art and science simultaneously and describe a new frame for the profession. In an effort to articulate and promote this new frame, this special issue was born. This introductory article concludes with a brief description of the topics and articles included in the issue to orient the reader to the content included within it.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/115-623-556-720-515 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Clinical judgment; Common elements; Common factors; Evidence-based practice; empirically-supported interventions; Research; dept.swk

Being known in undergraduate social work education: the role of instructors in fostering student engagement and motivation - Rodriguez-Keyes, Elizabeth; Schneider, Dana A; Keenan, Elizabeth King (Social Work Education, 2013)
Most undergraduate students pursue a social work major because of their desire to help others. Students tend to be more interested in doing than in understanding the research and knowledge of the profession and the complexities of social work practice. Instructors are often faced with the challenge of enhancing student motivation to learn challenging course material. This study explored student perceptions of instructor influences on their motivation and engagement in learning. Through online surveys, students described their experiences of being known and how those experiences affected their participation in practice, research, and human behavior in the social environment courses. Results showed that instructor caring (providing recognition, expressing relational qualities, and responding to students) positively influences student motivation and affective learning by increasing comfort, willingness to ask questions, take risks, and overall participation. Conversely, of those who reported mixed experiences or who felt unknown, most reported a negative impact on their motivation and participation. These findings suggest that social work faculty can influence student motivation and engagement with essential social work curriculum by expressing care and helping students feel known in the classroom. © 2013 Copyright Taylor and Francis Group, LLC.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-141-699-158-36X tex.type: [object Object]
Keywords: BSW Education; Being Known; Instructor Influence; Motivation; Student Engagement; dept.swk

Seeing Through the Eyes of the Other Using Process Recordings - Schneider, Dana A.; Rodriguez-Keyes, Elizabeth; Keenan, Elizabeth King (Clinical Supervision Activities for Increasing Competence and Self-Awareness, 2014)
This chapter describes a two-step process including videotaping and process-recording activities to facilitate self-awareness and the expression of empathy and acceptance toward other points of view. These activities are designed for beginning student clinicians who are currently completing their coursework and their first clinical internship. The first step of videotaping helps clinicians become more aware of their inner thoughts, feelings, beliefs, and personal values. This first step also helps participating clinicians become more aware of their nonverbal communication with clients, helping them assess how their internal experiences of empathy and acceptance match what is being conveyed nonverbally to their clients. The second step of the activity, process recording, helps clinicians reflect on their ability to use self-awareness to analyze their inner experiences and their outer expressions of empathy and acceptance (both verbal and nonverbal) while still being attuned to their clients' communication.
Section: 4 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781394259335.ch4
Keywords: dept.swk; nonverbal communication; process-recording activities; self-awareness; videotaping

Realizing the potential for leadership in social work - Keenan, Elizabeth King; Sandoval, Silvia; Limone, Christine (Journal of Social Work, 2019)
Ongoing racism, structural inequity, dehumanizing institutional bureaucracies, unresponsive service delivery systems, and gaps in services for emerging needs are just some of the pervasive challenges in need of social work leadership. The multidisciplinary nature of social work practice also requires value-based leadership processes on multiple ecological levels to address the challenges inherent within social delivery systems. Social work encourages all social workers to lead these change efforts, but research on front-line social work leadership is lacking. Constructionist conceptualizations of leadership as social influence processes provide a unit of analysis to examine front-line leadership. A secondary analysis of qualitative data examining social work practice that promotes well-being and social justice revealed leadership processes in multiple social work practice settings. Findings Front-line social workers demonstrate three overarching leadership processes in their practice: challenging injustice and changing mindsets, conduit for change, and organizing resources and relationships. Applications Conceptualizing leadership as social influence processes identifies and acknowledges the leadership of front-line social workers, expanding the profession's capacity to collectively articulate and initiate change with a range of social problems and systemic challenges in organizations and communities.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/137-713-768-820-865, pop00206 tex.type: [object Object]
Keywords: Social work; article; dept.swk; health care delivery; human; leadership; occupation; peer-reviewed; qualitative research; racism; secondary analysis; social constructionism; social justice; social work; social work practice; wellbeing

A "Just Sense of Well-Being": Social Work's Unifying Purpose in Action. - Keenan, Elizabeth King; Limone, Christine; Sandoval, Silvia L (Social work, 2017)
For over a century the social work profession has had a dual purpose, to promote both human well-being and social justice, but we have not found research that explores how social workers understand and work toward both purposes across multiple practice roles and settings. Authors of this article conducted qualitative research to examine how 18 social workers in various roles and settings understand and implement both purposes in their practice. Instead of a dual purpose, participants described a unifying purpose: a "just sense of well-being" that transcends role and setting. Valuing the dignity and worth of all human beings frames and fuels their work toward a just sense of well-being through three interactive themes: challenging injustice on every level; constructing justice through relationship and resource organizing; and constructing justice through the creation of accepting environments where professionals, clients, and community members can reflect and question, and change mind-sets and actions. Participants provided an array of possibilities for action with clients, professionals, and public leaders within organizations and communities. The implication here is that social workers are charged to reinvigorate purpose and values back into practice with value-based assessment thinking that frames possibilities for action across methods and settings. Copyright © 2016 National Association of Social Workers.
5 citations (Crossref) [2023-10-31] Place: United States Keenan, Elizabeth King. Department of Social Work, School of Health and Human Services, Southern Connecticut State University, New Haven, USA. Limone, Christine. Department of Social Work, School of Health and Human Services, Southern Connecticut State University, New Haven, USA. Sandoval, Silvia L. School for Social Work, Smith College, Northampton, MA, USA.
Keywords: *Professional Role/px [Psychology]; *Social Justice/px [Psychology]; *Social Work/mt [Methods]; *Social Workers/px [Psychology]; Adult; Female; Humans; Male; Middle Aged; Professional Role; Qualitative Research; Social Justice; Social Work; Social Workers; Social justice; Social work practice; Values; Well-being; adult; dept.swk; dual purpose; female; human; human dignity; human experiment; leadership; male; middle aged; occupation; organization; procedures; professional standard; psychology; qualitative research; social justice; social work; social work practice; social worker; thinking; wellbeing

Cacophony, polyphony or fugue: Exploring sociocultural concepts with social work students - Keenan, Elizabeth King; Miehls, Dennis; Moffatt, Kenneth; Orwat, John; White, Joyce (Smith College Studies in Social Work, 2004)
This paper documents some dialogue among the authors that emerged as each taught Master of Social Work students a course in sociocultural concepts. The instructors taught this required course from a common syllabus and the discussion reflects the authors' experiences in the delivery of the course material. At the time these dialogues took place, the instructors had recently changed the course format. Rather than teaching sociocultural concepts in isolation (eg. a class on sexism, a class on ageism, etc.), the instructors crafted the course content around central themes. Postmodern theories underscore much of the course content, and are synthesized both in this course and across the curriculum with feminist, psychodynamic, and cross-cultural practice theories. The paper begins by summarizing key post-modern theories that frame the course. Then, the authors respond to formulated questions that address multiple forms of identity development, ambiguity, and competing student ideologies that are manifest in classroom dynamics. Finally, the authors discuss their respective pedagogical and theoretical views and discuss their classroom experiences.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-164-803-188-190 tex.type: [object Object]
Keywords: dept.swk

Deepening the learning: Intersectional experiential activities to address white supremacy - Keenan, Elizabeth King; Kozu, Shuei; Mayhew, Hunter; Saiter-Meyers, Evelyn; Meggett, Caliyah; Reynolds, Paige (Advances in Social Work, 2021)
Graduate students of multiple racial identities in predominantly White institutions enter social work programs with a wide range of knowledge about and experiences of White Supremacy, particularly the ways in which structural forms of racism continue to inflict harm, block opportunities, and perpetuate wealth inequities. In addition, White students are often challenged to grasp the ways they have been socialized to participate in perpetuating White Supremacy. This wide range of knowledge and experiences makes it likely that students will experience a range of emotions and defensive resistance necessitating skillful pedagogical design and facilitation of class interactions. Intentional use of theoretical frameworks with experiential activities can deepen self-awareness and understanding of the systemic nature of White Supremacy (Okun, 2010). In this manuscript, four students and two instructors discuss their learning experiences within a course addressing White Supremacy for students of multiple racial identities in a predominantly White institution. Post-course dialogue amongst these multiracial authors identified six core areas of learning when examining intrapersonal, interpersonal, and structural racism, cultural wealth of BIPOC peoples, and anti-racism actions. Two primary implications for education are: Weave conceptual frameworks with interpersonal experiential activities throughout the course design, and attend to interactional power dynamics during class meetings. © 2021 Authors, Vol. 21 No. 2/3 (Summer 2021), 821-840,.
1 citations (Crossref) [2023-10-31] https://advancesinsocialwork.iupui.edu/index.php/advancesinsocialwork/article/view/24074 ; http://134.68.190.31/index.php/advancesinsocialwork/article/view/24074
Keywords: dept.swk; peer-reviewed

If Anti-Racism Is the Goal, Then Anti-Oppression Is How We Get There - Smith, Carmela Fusciello; Aguilar, Jemel P.; Kozu, Shuei; D'Angelo, Karen A.; Keenan, Elizabeth King; Tomczak, Stephen Monroe (Advances in Social Work, 2022)
Many schools of social work around the United States of America wrote anti-racism statements because of the recent murders of Black and Brown people. In this contribution, the authors describe a challenging and tense discussion of racism and anti-racism leading to a group process about oppression and anti-oppression in the social work profession. For some, the urgency to address racism led to tactics and strategies that got in the way of social workers engaging in anti-oppressive practices. While the structure of higher education often reinforces traditional hierarchies of power, the profession of social work calls us to promote our core values of social justice, integrity, and the importance of human relationships as we strive for an anti-oppressive future. Consequently, social work faculty may experience role conflict as we navigate these tensions. We believe it is important to harness and process such discomfort as we critically examine the power dynamics within our own department, and our own profession. This voluntary, ad hoc group, composed of a diverse group of faculty members, provides space for ongoing mutual aid, consciousness raising, appropriate discomfort, and accountability. If anti-racism is the goal, then anti-oppression is how we get there.
0 citations (Crossref) [2023-10-31] Number: 2
Keywords: White supremacy; dept.swk; peer-reviewed